Źródła wiedzy polskich przedsiębiorstw o rynku Unii Europejskiej i sposoby ich pozyskiwania - Burlita, Augustyna; Witek, Jolanta (Sources of Knowledge of Polish Enterprises about EU Market and Ways of Winning It over, 2006)
The integration of Poland with EU set new challenges for Polish enterprises. A necessary competitive struggle and possibility of work on the union market, create a demand for information about the EU market. Firm's success will be more and more dependent on a skill to win necessary information over, to use it and on knowledge, competence to learn and special cognitive attitudes.The article presents the main research results carried out among enterprises of West Pomerania on the appraisal made by them of the integration process and their state of knowledge about the EU market, the knowledge's sources and the way of winning it over.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 177-186